2003
DOI: 10.1089/088922203322230905
|View full text |Cite
|
Sign up to set email alerts
|

polGene Sequence Variation in Swedish HIV-2 Patients Failing Antiretroviral Therapy

Abstract: There is limited knowledge about how to treat and interpret results from genotypic resistance assays in HIV-2 infection. Here, genetic variation in HIV-2 pol gene was studied in 20 of 23 known HIV-2 cases in Sweden. Five patients with signs of virological treatment failure were longitudinally studied. Clinical, virological and immunological data were collected and the protease (PR) and first half of the reverse transcriptase (RT) was amplified and directly sequenced from plasma samples. Moderate to extensive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 18 publications
8
35
1
Order By: Relevance
“…Apart from the ZDV-associated secondary mutations V75I and K219Q/E, present as natural polymorphisms, other ZDV mutations have not been found in any of the patients. As previously observed, accumulation of the six thymidine analogue resistance mutations, M41L, D67N, K70R, L210W, T215Y, and K219Q/E (32), marking classic ZDV resistance in HIV-1 (1,6,9,23,49), was also absent in the HIV-2 sequences. Therefore, we conclude that high-level resistance to 3TC also contributed to the virological failure observed for patients 2 and 11 and that the viruses in these patients either are sensitive to ZDV or have as yet unidentified ZDV-associated mutations.…”
Section: Vol 47 2009 Haart and Drug Resistance In Hiv-1 And Hiv-2 Isupporting
confidence: 75%
See 1 more Smart Citation
“…Apart from the ZDV-associated secondary mutations V75I and K219Q/E, present as natural polymorphisms, other ZDV mutations have not been found in any of the patients. As previously observed, accumulation of the six thymidine analogue resistance mutations, M41L, D67N, K70R, L210W, T215Y, and K219Q/E (32), marking classic ZDV resistance in HIV-1 (1,6,9,23,49), was also absent in the HIV-2 sequences. Therefore, we conclude that high-level resistance to 3TC also contributed to the virological failure observed for patients 2 and 11 and that the viruses in these patients either are sensitive to ZDV or have as yet unidentified ZDV-associated mutations.…”
Section: Vol 47 2009 Haart and Drug Resistance In Hiv-1 And Hiv-2 Isupporting
confidence: 75%
“…Generally, fewer mutations accumulated in these HIV-2 patients with viral rebound than in those from previous studies (1,6,9,23), and the Q151M mutation was absent. This finding indicates that efficient therapy results in fewer mutations and therefore less cross-resistance to other drugs.…”
Section: Vol 47 2009 Haart and Drug Resistance In Hiv-1 And Hiv-2 Icontrasting
confidence: 51%
“…Wild-type HIV-2 RT contains Ser instead of Thr at position 215, and only one nucleotide change is needed to obtain the substitution S215Y. However, Q151M emerges as the major AZT resistance mutation in HIV-2 RT, whereas TAMs are relatively uncommon in HIV-2-infected patients (72)(73)(74). Molecular modeling studies suggested that several amino acid differences around the putative ATP binding site of HIV-2 RT in comparison with the HIV-1 RT could account for these differences (75).…”
Section: Discussionmentioning
confidence: 99%
“…The 26 samples from The Netherlands were from 16 treatment-experienced HIV-2-infected patients, mostly of West African origin, who were genotyped at the Erasmus Medical Centre in Rotterdam, The Netherlands. The 30 Swedish samples were from 12 patients-6 untreated, 1 treated successfully, and 5 failing therapy-as previously described (8). These samples were selected from 20 of 23 known cases of HIV-2 in Sweden.…”
Section: Patientsmentioning
confidence: 99%
“…These samples were selected from 20 of 23 known cases of HIV-2 in Sweden. Most of these patients were immigrants from different West African countries (8).…”
Section: Patientsmentioning
confidence: 99%